Improvement of Basic Volleyball Techniques through Motion Coordination Learning Model: A Literature Review - Nova Risma; Syahrial Bakhtiar; Umar (Universitas Negeri Semarang, 2024)
The learning model based on movement coordination is believed to improve the basic skills of volleyball more optimally. Therefore, a literature review is needed to analyze the effectiveness of the movement coordination learning model in improving the basic technique of volleyball. This study aims to examine and analyze various models of movement coordination learning that have been applied in volleyball training and their impact on improving players' basic techniques. This study uses a literature review method by analyzing various journals, books, and scientific articles that discuss the learning model of movement coordination in sports, especially volleyball. The sources of literature used come from relevant research in the last 10 years. The analysis was carried out by reviewing the effectiveness of the movement coordination learning model on the development of basic techniques of volleyball players. Based on the literature review conducted, it was found that the learning model based on movement coordination had a positive impact on improving the basic techniques of volleyball. This model is able to improve motor skills, balance, and player response speed in match situations. In addition, this learning approach also supports the improvement of tactical understanding and game strategy through more varied and dynamic exercises. The movement coordination learning model has proven to be effective in improving the basic technique of volleyball. With the right application, this model can help players in developing technical and motor skills more optimally. Therefore, sports coaches and educators are advised to integrate this model in training programs to improve the quality of volleyball learning.